2016
DOI: 10.5943/mycosphere/si/3b/3
|View full text |Cite
|
Sign up to set email alerts
|

Mycosphere Essay 11: Fungi of Pycnoporus: morphological and molecular identification, worldwide distribution and biotechnological potential

Abstract: Fungi of the Pycnoporus are efficient degraders of lignocellulosic materials, so they are classified as white-rot fungi. A distinctive feature is its color ranging from orange to bright red, attributed to cinnabarin, cinnabarinic acid and tramesanguin mainly, compounds to which have been attributed some biological activities. This review updates the reports on morphological characteristics, the distribution of species of Pycnoporus, and the advantages of molecular techniques in species identification. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
4
16
0
3
Order By: Relevance
“…The high biomass yield in 20-and 25-day-old cultures is most likely attributed to the very thick mycelia and formation of primordia. The same cultural characteristics of P. sanguineus were also observed by Tellez-Tellez et al [20]. They observed that the presence of salmon-red color or vermillion pigment becomes more intense as the mycelia aged, and they also believed that this characteristic greatly participates in bioactivities of the mycelia.…”
Section: Mycelial Biomass Productionsupporting
confidence: 74%
See 1 more Smart Citation
“…The high biomass yield in 20-and 25-day-old cultures is most likely attributed to the very thick mycelia and formation of primordia. The same cultural characteristics of P. sanguineus were also observed by Tellez-Tellez et al [20]. They observed that the presence of salmon-red color or vermillion pigment becomes more intense as the mycelia aged, and they also believed that this characteristic greatly participates in bioactivities of the mycelia.…”
Section: Mycelial Biomass Productionsupporting
confidence: 74%
“…They observed that the presence of salmon-red color or vermillion pigment becomes more intense as the mycelia aged, and they also believed that this characteristic greatly participates in bioactivities of the mycelia. Pigment characterization and biosynthesis revealed that phenoxazine-3-one type structure is the one accountable for the red color pigment of several Pycnoporus strains and for their bioactivities [20,21].…”
Section: Mycelial Biomass Productionmentioning
confidence: 99%
“…This color comes from the synthesis of various pigments of phenoxazine-3-one type, including cinnabarin, cinnabarinic acid and tramesanguin (Sullivan & Henry 1971). According to Téllez-Téllez et al (2016), there are two other pigments of phenoxazine-3-one type i.e., ɑ-Aminuophenoxazone and Pycnoporin.…”
Section: Kantor Penyuntingmentioning
confidence: 99%
“…Jamur ini memiliki persebaran yang luas mulai dari daerah temperate hingga tropis dan memiliki tubuh buah yang mampu bertahan sepanjang tahun (Téllez-Téllez, 2016). Hingga saat ini tercatat sebanyak 13 spesies, subspesies, dan varietas dari Pycnoporus di seluruh dunia (http://www.indexfungorum.org/Names/Names .asp, diakses pada 01 Agustus 2020).…”
Section: Pycnoporuscf Sanguineusunclassified